Pengaruh Beban Kerja, Kepuasan Kerja dan Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan di Sektor Akuntansi dan Keuangan PD. Karya Bearing Motor Bekasi - Joko Setyawan; Heru Budi Santoso; Dedi Muliadi; Wahyu Leman (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the influence of workload on employee performance, the effect of job satisfaction on employee performance, and work discipline on employee performance. The unit of analysis of the research is PD. Karya Bearing Motor Bekasi, Data collection was carried out by distributing questionnaires, with a total of 25 respondents. This study uses a descriptive method through a quantitative approach with the help of SPSS version 27. The results of the study show that the value of sig. The workload variable is 0.741 > 0.05, the workload variable has no effect on employee performance. The value of sig. Of the job satisfaction variables, which are 0.868 > 0.05, the job satisfaction variable has no effect on employee performance. The value of sig. From the work discipline variables, which are 0.989 > 0.05, the work discipline variable has no effect on employee performance. Then simultaneously the variables of workload, job satisfaction, and work discipline have no effect on the performance of PD employees. Karya Bearing Motor.